Romano Guardiniego ponowożytny obraz świata - Rossa, Piotr (Stowarzyszenie Teologów Fundamentalnych w Polsce, 2013)
The article presents a postmodern view of the world, as it is seen by Romano Guardini, one of the most important 20th century theologians of Italian and German descent. Gaurdini, who looks at the postmodern reality as a whole, notes a deep de-Christianization of the vision of man, his culture and his world. Nevertheless, Guardini expresses the hope that the postmodern Christian will be more radically guided by faith and trust in God’s action.
Romano Guardini’s Postmodern View of the World
Keywords: Romano Guardini; postmodernity; kultura; człowiek; świat; freedom